Utilizing Social Media Data for Psychoanalysis to Study Human Personality - Emmert-Streib, Frank; Yli-Harja, Olli; Dehmer, Matthias (Frontiers in Psychology, 2019)
Social media data, for instance from Twitter or Facebook, provide a new type of data that consist of a mixture of text, image and video information. From a scientific point of view, the capabilities of this type of data from such microblogs are not well explored and to date it is largely unknown what principal knowledge can be extracted thereof. In this paper, we present a discussion of the capabilities of data from microblogs for performing a psychoanalysis. This could allow an analysis of the human personality of individual users. Such prospects raises serious concerns regarding the privacy of users of social media platforms.